GREEN CONSTITUTION INDONESIA (DISKURSUS PARADIGMATIK PEMBANGUNAN BERKELANJUTAN) - Lucas Prabowo (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2014)
Efforts to meet the economic needs of humans has resulted in severe damage to the ecosystem. Being aware that there is damage to natural resources and ecosystem are getting worse, various efforts underway to hold international conventions in the field of environmental protection has resulted in agreements, both of which are binding (hard law) and non-binding (soft law). Participating countries adopted the convention rules agrred up on into their legaislation, and even to strengthen the protection and enforcement of laws relating to environmental protection and the right to a good environment for the present dan future generations, environmental norms are then contained in the constitution including the Indonesian constitution, namely the post-UUD 1945 amandement. Keywords: environmental damage, international environmental law damage, intergerational equity, sustainable development, and constitution.